EFEKTIFITAS MODEL PEMBELAJARAN JIGSAW DALAM MENGELOLA PARTISIPASI AKTIF SISWA KELAS IV PADA PEMBELAJARAN IPA DI MI AR RAUDHAH SAMARINDA - Yuda Rosado; Abdul Razak; Maulida Ulfa Hidayah; Khonsaullabibah Maisun Nur Rifdah; Miranda (Studies in Advanced Pedagogy and Academic Understanding, 2024)
The jigsaw learning model is useful for helping students develop cooperation skills, critical thinking and the ability to help friends. This learning will create students to participate and be active so that students will think together, discuss together, conduct investigations together and act in the same direction. The aim of this research is to determine the effectiveness of the jigsaw learning model in managing the active participation of class IV students at MI Ar Raudhah Samarinda. This type of research is quantitative with experimental research methods and quasi-experimental designs. The population in this study were class IV students at MI Ar Raudhah Samarinda for the 2021/2022 academic year. The sampling technique was saturated, with a sample of 46 students. Data collection techniques use observation, documentation and questionnaires. Data rejuvenation test techniques are Normality Test, Homogeneity Test and Hypothesis Test. Based on the research results, it shows that the effective application of the jigsaw model in science learning material on animal breeding can manage the active participation of class IV students at MI Ar-Raudhah Samarinda by obtaining a Sig (2-tailed) value, namely 0.026 < 0.05 and a tcount > ttable, namely 2.329 > 1.681 which makes the Ha hypothesis accepted